ONLINE COMMUNITY AS A MEANS OF COMMUNITY EMPOWERMENT THROUGH LECTURER AND STUDENT SERVICE ACTIVITIES - Helleri Fivtrawati (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2022)
The high number of Covid-19 spreads in Indonesia has had an impact on all sectors. various things to break the chain of the spread of COVID-19 including physical distancing or physical distance restrictions from humans. This of course will limit and become an obstacle for the implementation of various activities that require direct face-to-face meetings, including community service. In this community service, this health education activity is carried out in the form of health with the theme of the activity "Let's Like to Wash Hands" with ZOOM and YouTube media. Implementation of health education activities using storytelling methods, hand washing education. The presenters gave fairy tales and education about hand washing to children. After that, discussion and question and answer were held. implementation time is Sunday, September 30, 2021 through the Zoom meeting room application. This service has been carried out online through the Zoom Meeting application with a total number of 42 participants, consisting of 10 committee members and 30 respondents. The results of the average percentage of all indicators of 92% indicate that the "Let's Like to Wash Hands" activity went very well. Conclusion: The activity “Let's Like to Wash Hands” went very well, participants gained information about the importance of washing hands and how to wash hands properly.